Separation anxiety in PTSD: A pilot study of mechanisms in patients undergoing IPT. Issue 4 (25th February 2020) - Milrod, Barbara; Keefe, John R.; Choo, Tse‐Hwei; Arnon, Shay; Such, Sara; Lowell, Ari; Neria, Yuval; Markowitz, John C.
Abstract: Introduction: Separation anxiety disorder (SAD) comprises one aspect of attachment dysregulation or insecurity. Although SAD aggravates posttraumatic stress disorder (PTSD) risk, no clinical research has tracked how many patients with PTSD have SAD, its clinical associations, or its response to PTSD treatment. Our open trial of interpersonal psychotherapy (IPT) for veterans with PTSD assessed these SAD domains. Methods: Twenty‐nine veterans diagnosed with chronic PTSD on the Clinician‐Administered PTSD Scale were assessed for SAD using the Structured Clinical Interview for Separation Anxiety Symptoms (SCI‐SAS), and for Symptom‐Specific Reflective Function (SSRF), another dysregulated‐attachment marker capturing patients' emotional understanding of their symptoms. Patients received 14 IPT sessions for PTSD with assessments at baseline, Week 4 (SCI‐SAS and SSRF), and termination for SAD, PTSD, and depression. Results: At baseline, 69% of patients met SAD criteria. Separation anxiety did not correlate with baseline PTSD severity, depressive severity, or age when traumatized; patients with and without SAD had comparable PTSD and depression severity. Patients with baseline comorbid SAD who completed IPT ( N = 17) reported significantly improved adult separation anxiety ( p = .009). Adult SAD improvements predicted depressive improvement ( p = .049). Patients with SAD showed a stronger relationship between early SSRF gains and subsequent adult SAD improvement ( p = .021) compared with patients without SAD. Discussion: This first exploration of dysregulated/insecure attachment features among patients with PTSD found high SAD comorbidity and adult SAD improvement among patients with SAD following IPT. Highly impaired attachment patients normalized attachment posttreatment: 14‐session IPT improved attachment dysregulation. This small study requires replication but begins to broaden clinical understanding of separation anxiety, attachment dysregulation, and PTSD.